QCM-D Studies on Polymer Behavior at Interfaces - Liu, Guangming. (SpringerBriefs in Molecular Science,, 2013)
QCM-D Studies on Polymer Behavior at Interfaces reviews the applications of quartz crystal microbalance with dissipation (QCM-D) in polymer research, including the conformational change of grafted polymer chains, the grafting kinetics of polymer chains, the growth mechanism of polyelectrolyte multilayers, and the interactions between polymers and phospholipid membranes. It focuses on how QCM-D can be applied to the study of polymer behavior at various solid-liquid interfaces. Moreover, it clearly reveals the physical significance of the changes in frequency and dissipation associated with the different polymer behaviors at the interfaces.